2017
DOI: 10.1016/j.dental.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship of microstructure and hardness of human coronal dentin using reference point indentation technique and micro-Raman spectroscopy

Abstract: Objectives The aim of this paper is to determine the interrelationship between the microstructure--in terms of chemical composition and crystallinity--to the microhardness of coronal dentin. Methods Dentin microhardness was tested by a novel reference point indenter and compared to the traditional Knoop hardness method. Micro-Raman spectroscopy was used to determine the chemical composition and crystallinity of dentin. Results From the occlusal groove to the border of the coronal pulp chamber, dentin hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In this study the hardness values of normal dentin were in good agreement with the previous studies of dentin [32,33]. And in our studies, the element P in DGI-dentine shown a lower level compared with normal dentine, which verify the positive association between dentin hardness and mineral content [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…In this study the hardness values of normal dentin were in good agreement with the previous studies of dentin [32,33]. And in our studies, the element P in DGI-dentine shown a lower level compared with normal dentine, which verify the positive association between dentin hardness and mineral content [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, we have also observed that the quality of mineralization in DGI-I dentine was far from satisfactory. First, the dentine hardness and collagen elasticity in the proband were significantly lower than in the control samples (p < 0.05), which was consistent with the clinical high brittleness phenomenon (Seyedmahmoud et al, 2017). Meanwhile, the hardness values of the control dentine were in good agreement with the results of previous studies on dentine (Fawzy et al, 2017;Yi et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The determined ν1()normalPO43 peak FWHM values were different between superficial and deep dentine, located near the enamel‐dentine junction and at the border of the coronal pulp chamber, respectively. The results showed a significant increase in FWHM in dentine near the pulp region, which was attributed to structural disorder …”
Section: Resultsmentioning
confidence: 99%